Analisis Proyek Fabrikasi Truss Frame menggunakan Metode Critical Path Method (CPM) dan Project Evaluation Review Technique (PERT) di PT PQR - Wauran, Andreas Fernandez; Winarno, Winarno (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
The construction industry continues to grow rapidly, making quality and punctuality essential in completing projects on time. Effective time management plays a key role in minimizing delays. This study focuses on a Truss Frame fabrication project at PT PQR, which was initially planned for 26 working days but ultimately required 326 working hours due to early delays. While the project still met the client's deadline, the delay posed a risk to other company projects. To optimize scheduling, the study applied the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT). The analysis showed that CPM reduced the project duration to 314 hours, whereas PERT resulted in 319 hours with a 79% success probability. Compared to the actual 326-hour duration, CPM provided a 12-hour time reduction, making it the more efficient method. The project’s critical path was A-B-D-E-F-G-H-I-J, with activity C (Cutting Plan) requiring completion before the 88th hour. These findings highlight CPM’s effectiveness in optimizing Truss Frame project scheduling at PT PQR. Keywords: CPM, Construction Project, PERT, Project Management